Transcriptional profiling of a fungal granuloma reveals a low metabolic activity of Paracoccidioides brasiliensis yeasts and an actively regulated host immune response - Borges, Bruno Montanari; Ramos, Rafael Berton Correia; Preite, Nycolas Willian; Kaminski, Valéria de Lima; Alves de Castro, Patrícia; Camacho, Maurício; Maximo, Marina Ferreira; Fill, Taicia Pacheco; Calich, Vera Lúcia Garcia; Traynor, Aimee M.; Sarikaya-Bayram, Özlem; Doyle, Sean; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Granulomas are important immunological structures in the host defense against the fungus Paracoccidioides brasiliensis, the main etiologic agent of Paracoccidioidomycosis (PCM), a granulomatous systemic mycosis endemic in Latin America. We have performed transcriptional and proteomic studies of yeasts present in the pulmonary granulomas of PCM aiming to identify relevant genes and proteins that act under stressing conditions. C57BL/6 mice were infected with 1x10 6 yeasts and after 8-and 12-weeks of infection, granulomatous lesions were obtained for extraction of fungal and murine RNAs and fungal proteins. Dual transcriptional profiling was done comparing lung cells and P. brasiliensis yeasts from granulomas with uninfected lung cells and the original yeast suspension used in the infection, respectively. Mouse transcripts indicated a lung malfunction, with low expression of genes related to muscle contraction and organization. In addition, an increased expression of transcripts related to the activity of neutrophils, eosinophils, macrophages, lymphocytes as well as an elevated expression of IL-1β, TNF-α, IFN-γ, IL-17 transcripts were observed. The increased expression of transcripts for CTLA-4, PD-1 and arginase-1, provided evidence of immune regulatory mechanisms within the granulomatous lesions. Also, our results indicate iron as a key element for the granuloma to function, where a high number of transcripts related to fungal siderophores for iron uptake was observed, a mechanism of fungal virulence not previously described in granulomas. Furthermore, transcriptomics and proteomics analyzes indicated a low fungal activity within the granuloma, as demonstrated by the decreased expression of genes and proteins related to energy metabolism and cell cycle.